Prevalence of metabolic syndrome in type 2 diabetes mellitus patients using NCEP/ATP III and IDF criteria in Nepal - Bhattarai, S; Kohli, SC; Sapkota, S (Nepal Journal of Medical Sciences, 2012)
Background: With increasing trends towards sedentary life style, obesity, diabetes mellitus, hypertension, and dyslipidaemia, the prevalence of metabolic syndrome (MetS) is rising in our country. In view of importance of diagnosis of MetS in day to day medical practice for early institution of life style therapies to reduce the atherosclerotic cardiovascular disease risk in susceptible population like in diabetes mellitus, this study has been undertaken to study the prevalence of metabolic syndrome in Nepalese diabetes by applying National Cholesterol Education Programme/Adult Treatment panel (NCEP/ATP) III and International Diabetes Federation (IDF) criteria. Methods: This is a hospital based cross sectional study conducted in diabetes patients aged between 25-75 years of age presenting to Manipal Teaching Hospital, Pokhara. Different components of MetS were studied in diabetes subjects and prevalence of metabolic syndrome was obtained by applying NCEP/ATP III and IDF criteria respectively. The data were collected as per preformed proforma and results analyzed by SPSS-16 software. Results: The prevalence of metabolic syndrome in diabetes patients as per NCEP/ATP III and IDF criteria were 71% and 82% respectively. A higher number of cases with metabolic syndrome were detected using IDF criteria as opposed to NCEP/ATP III criteria in diabetes patients. Nepalese diabetes subjects showed high prevalence of abdominal obesity followed by hypertension. Conclusions: The results of the present study show high prevalence of Mets in Nepalese diabetes patients and more number of cases can be diagnosed by applying IDF criteria as compared to NCEP/ATP III criteria. DOI: http://dx.doi.org/10.3126/njms.v1i2.6604 Nepal Journal of Medical Sciences. 2012;1(2): 78-83